CRIMINAL LIABILITY OF A DOMESTIC ASSISTANT WHO COMMITS THE CRIME OF THEFT IN THE EMPLOYER'S HOUSE BY DUPLICATING THE ROOM KEY - Putri, Marsanda; Ramasari, Risti Dwi; Seftiniara, Intan Nurina (Fakultas Hukum Universitas Djuanda, 2024)
Theft according to Decision Number: 719/Pid.B/2023/PN. The incident, in which the perpetrator was the victim's domestic assistant (hereinafter abbreviated as ART), began on Friday, June 16, 2023, when the witness Desi Laurina took the witness's child to therapy in Solo for 20 days normative legal norm method of legal research, namely the review of the results of an investigation into the criminal liability of a domestic servant who commits the crime of theft, through a review of various literature, not limited in time and place, as well as a review of various literature in the form of books in the employer's house Duplicating room keys based on Decision No. 719 /Pid.B/2023/PN Tjk. Acts committed by the accused shall be punished with a prison sentence of 2 months and 20 days, as determined by the panel of judges of the Tanjungkarang District Court Class 1 A on September 18, 2023. And the judge's considerations when deciding on this perpetrator of the crime of theft in the employer's house by duplicating the room key on the basis of Decision No. 719/Pid.B/2023/PN Tjk. It is unreasonable and does not comply with the provisions of current laws and regulations, and the author believes that the jury's verdict is too lenient for the perpetrator who committed the crime of theft, causing public unrest and the employer causes harm to the defendant, so that no deterrent effect can be achieved for the perpetrator. Suggestions for law enforcement officers to take appropriate measures regarding the crime of theft and provide strict legal sanctions because the theft committed by the accused is very harmful to other people and disturbs the community. However, the sentence imposed is only two months in prison